A Comprehensive Analysis on Transient Electromagnetic Force Behavior of Stator Windings in Turbo-Generator. (22nd October 2018) - Jiang, Hong-Chun; He, Yu-Ling; Tang, Gui-Ji; Xu, Ming-Xing
Abstract : This paper presents a comprehensive analysis on the transient electromagnetic force behavior of the stator windings in a QFSN-600-2YHG type turbo-generator. Different from other studies, this paper investigates not only the distribution regularities of the resultant force and the force density, but also the force harmonic characteristics, and the mechanical responses which will cause sensitive impact on the insulation wearing. The whole work is generally based on a proposed simplified model and the 3D finite element coupling calculation. The simplified model contains two parts. The first part is the theoretical model that employs the approximate solution of the image current to obtain the analytic formula of the electromagnetic force on the end windings conveniently. The second part is the FEA model that employs only the end windings and one-tenth of the stator core to save the calculating memory and, meanwhile, obtain the qualified electromagnetic force as well as the mechanical response. It is shown that the nose-top, the connection point between the line part and the end part, and the middle of the involute are the three most dangerous positions of the end winding to sustain serious insulation wearing. Moreover, the winding, which endures the maximum mechanical response, is neither always consistent with the one that has the largest resultant electromagnetic force nor directly in accordance with the winding that affords the most intensive electromagnetic force density. The findings in this paper will be beneficial for the insulation monitoring and the manufacturing improvement on the stator windings.